2019
DOI: 10.1016/s0140-6736(19)31146-8
|View full text |Cite|
|
Sign up to set email alerts
|

Oral diseases: a global public health challenge

Abstract: Oral diseases are among the most prevalent diseases globally and have serious health and economic burdens, depriving people of health, wellbeing, and the ability to achieve their full potential. By virtue of their high prevalence, the most consequential oral diseases affecting global health are: dental caries, periodontal disease, tooth loss, and cancers of the lips and oral cavity. In this first of two papers, we describe the scope of the global oral disease epidemic, describe its origins in social and commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
2,003
3
142

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,310 publications
(2,171 citation statements)
references
References 122 publications
23
2,003
3
142
Order By: Relevance
“…Thus, our results may not apply to all older adults, such as hospitalized patients or those requiring long‐term care. However, it should be noted that oral diseases persist with high prevalence, reflecting widespread social and economic inequality and inadequate funding for prevention and treatment, particularly in low‐income and middle‐income countries . Because Japan is a high‐income country, the results of this study may not apply to low‐income and middle‐income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results may not apply to all older adults, such as hospitalized patients or those requiring long‐term care. However, it should be noted that oral diseases persist with high prevalence, reflecting widespread social and economic inequality and inadequate funding for prevention and treatment, particularly in low‐income and middle‐income countries . Because Japan is a high‐income country, the results of this study may not apply to low‐income and middle‐income countries.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, 91% of American adults aged 20‐64 experienced dental caries . Untreated dental decay adversely affects quality of life, social relations and health . Further, direct oral healthcare expenditures in the United States are significant, exceeding $105 billion .…”
Section: Introductionmentioning
confidence: 99%
“…1 Untreated dental decay adversely affects quality of life, social relations and health. 2,3 Further, direct oral healthcare expenditures in the United States are significant, exceeding $105 billion. 4 Coronal caries forms throughout the lifespan 5,6 and is the primary cause of tooth loss in older adults, accounting for most of older adults' oral health expenditures.…”
Section: Introductionmentioning
confidence: 99%
“…Oral diseases, including tooth decay, gum disease and oral cancers, affect almost half of the global population, with untreated dental decay the most common health condition worldwide. Despite this substantial burden, integrated oral healthcare pathways within the general medical pathway have been neglected with calls for radical reform of dental care systems whose models have failed to combat the global challenge of oral diseases which is rarely included in universal health coverage …”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in other areas of medicine, the prevalence of oral disease continues to increase in low‐income and middle‐income countries, and among socially disadvantaged and vulnerable people, no matter where they live. Therefore, tooth extraction remains among the most frequent invasive procedures in general population . It is likely to be the most common surgical procedure required in people with haemophilia (PWH), especially those living in countries with restricted resources: a recent report looking at patient reported outcomes in haemophilia suggested that the mouth was the single most common site of perceived life‐threatening bleeding amongst those individuals…”
Section: Introductionmentioning
confidence: 99%